A Case Study on School Innovation and Change - Walker, Aneta (Advances in Social Sciences Research Journal, 2020)
The implementation of the rigorous, complex Common Core State Standards (CCSS) has prompted schools to initiate change in traditional organizational structures. The CCSS have required teachers to have a deeper understanding of subject matter and specialized content instruction to effectively teach the standards. There is a vast amount of research on educational change as related to school improvement, however, this research analyzed how schools create a context for change to implement a new innovation and improve the learning environment. The purpose of this research study was to evaluate the effectiveness of an innovative hybrid schedule in improving student learning outcomes and school culture. This mixed-method research study used data generated by the Stages of Concern Questionnaire (SoCQ), AdvancEd®’s Stakeholder Feedback Survey, ACT Aspire® Student Achievement Tests, and teacher interviews. The conceptual framework of the case study was based on the five attributes of the PLCs identified through the work of Shirley M. Hord (2004) and Michael Fullan’s Educational Change Theory (2007). The results of this study indicated the implemented innovation had a significant impact on school culture based on the two administrations of the AdvancEd®’s Stakeholder Feedback Survey. Additionally, student learning outcomes measured by ACT Aspire® Reading and Mathematics Student Achievement Tests showed statistically significant improvements in both reading and math. Lastly, the analysis of teacher interviews supported the findings in the quantitative data.